21st Century Virtual Language Learning Environments (VLLEs). Issue 8 (August 2014) - Mroz, Aurore
Abstract Learning a foreign language (L2) has never been more efficiently done than through immersion in the target culture. By comparison, learning in a traditional classroom has proven to lead only to limited proficiency. But traveling to the target country is still inaccessible for many L2 learners. Investing in the tremendous array of technologies that have emerged since the beginning of the 21st century could bring us one step closer. This essay overviews the body of research on Virtual Language Learning Environments (VLLEs), considered as promising venues to approximate the type of naturalistic learning that happens in real‐life immersion. Drawing on research in Computer‐Assisted Language Learning (CALL) and Second Language Acquisition (SLA) theories, this paper intends to provide a clearer picture of what virtuality entails for the L2 learning process, and to offer research‐based suggestions on what to look for to integrate VLLEs in the L2 curriculum.